Surve Tingkat Pemahaman terhadap Pelatihan Penggunaan Goggle Formulir untuk Mahasiswa Pendidikan Jasmani - Achmad Afandi; Titik Purwati; Rizka Hadiwiyanti (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2026)
This community service activity aimed to assess students' level of understanding regarding training on the use of Google Forms as a tool to support learning and academic data collection. The study was conducted at Universitas Insan Budi Utomo Malang, involving students from Class D. A quantitative descriptive research method using a survey approach was employed. The study population consisted of 1,000 students, while the sample comprised 31 students selected via simple random sampling. A Likert-scale questionnaire served as the research instrument to measure aspects of student understanding regarding Google Forms usage. Data were analyzed using descriptive statistics specifically percentages to illustrate the respondents' level of understanding. The results indicate that the majority of students possessed a good level of understanding regarding the use of Google Forms following the training. Students demonstrated an understanding of the processes involved in creating forms, formulating questions, configuring form settings, distributing links, and managing response data. Thus, the Google Forms training was effective in enhancing student understanding and serves as a viable alternative for developing digital competence within the higher education environment.